Universal Health Coverage in India: Where Rubber Hits the Road? - Devajana Chinnappa Nanjunda (Annals of the National Academy of Medical Sciences (India), 2020)
Poverty and healthcare issues are the most debatable topics today. Developing countries like India have as much as 45% of its population trapped in poverty because of various urgent healthcare needs. Universal health coverage (UHC) is a unique insurance system to provide financial protection to the marginalized groups of the country. It facilitates appropriate and immediate health needs, including required diagnostic, therapeutic and operational costs. However, UHC, a unique plan which focuses on the disadvantaged sections of the society, has some serious lacunae when it comes to its implementation in real life. This includes finances and human resources. Experts are reallocating adequate budgetary expenditure on healthcare issues, and in the meantime, a shortage of skilled health manpower is hunting down the UHC scheme in India. In recent times, different state governments are increasing budget allocation for the health sector. UHC is targeting low-income and poor families, forgetting the affordable and timely healthcare by way of improving services offered at the primary health centers and rapid expansion of the skilled health manpower across the country. UHC needs to focus on health paradigm systems, including improved healthcare-seeking behavior, nutrition, sanitation, potable water, reducing maternal and infant mortality, and dissemination of information of current technology to provide quality health services to the underserved and marginalized population of the country. These changes would symbolize a real way forward toward the immediate fulfillment of UHC goals for India.